Entre Prospero et Caliban: du caractère hybride de Camus - Gomes, Fernando (2012)
Between Prospero and Caliban: about Camus’ hybrid character. The exegesis of Le Premier Homme, unfinished novel biographic in essence, is fundamental for the study of the camusian dialogues with the alterity. In fact, the search for affirmation of identity, essential theme in Le Premier Homme, is build upon a feeling of a double alienation towards the French from the metropole as well as towards the natives. The identification of the author as “Pied–noir” is constructed around a cultural and religious emptiness – “without memory and without faith”-, and around the ambivalence of his relationship with the native population. This paper aims to demonstrate that in the few pages of the chapter “Obscur à soi-même”, title indicative of the illusion of the search for identity, the “other” is perceived as a human being constitutive of his identity, as an integrating part of his “obscure and interlaced roots”. The reading of this narrative allows the confirmation the identity of a man torn apart by his political convictions and his feelings towards Argelia. In conclusion, Camus is actually, the fruit of a cultural and historical emptiness distinctive of the French from Argelia, that “bastard race, made of unexpected mixtures”, an hybrid individual, between Prospero and Caliban, made by the country where he was born and grown-up, and by the presence of the native which he loved and respected as his equal, but which marked his imaginary, his unconscious as a figure of the “other”, incomprehensible and frightening; ancestral fears derived from orientalist imagery that inhibit the existence of deep relations between communities.